The Influence of Emotional Intelligence and Spiritual Intelligence on Teacher Professionalism at the Working Group of Madrasah Seputih Banyak - Sunanto, Sunanto; Mispani, Mispani; Setiawan, Dedi (CV. Creative Tugu Pena, 2022)
The article was to analyze the effect of emotional intelligence on teacher professionalism, the influence of spiritual intelligence on teacher professionalism, and the influence of emotional intelligence and spiritual intelligence on teacher professionalism. The method used descriptive quantitative through data collection techniques questionnaires and interviews. Analyzing data used multiple regression. The result showed that emotional intelligence has an effect on teacher professionalism at Seputih Banyak Madrasah Working Group, Central Lampung Regency. Spiritual intelligence affects the professionalism of teachers in the Working Group of Madrasah Seputih Banyak, Central Lampung Regency.. Emotional intelligence together with spiritual intelligence has an effect on Teacher Professionalism in the Working Group of Madrasah Seputih Banyak, Central Lampung Regency. From the results of the hypothesis test, it is known that the significance value for the influence of emotional intelligence and spiritual intelligence simultaneously (together) on teacher professionalism with F count > F Table with Fcount (18.369) and Ftable (3.18), so it can be interpreted that Fcount (18.369) > Ftable (3.18) it can be concluded that emotional intelligence and spiritual intelligence have an effect on teacher professionalism and the probability value is 0.05 greater and a significant value is 0.000 or a value of 0.05 > 0.000 this it can be concluded that emotional intelligence and spiritual intelligence are significant to teacher professionalism Keywords : Teacher Profesionalism, Emotional Intelegence, Spiritual Intelegence